2005
DOI: 10.1007/s00535-004-1505-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of apoptotic cell death in systemic complications with severe acute pancreatitis

Abstract: In severe acute pancreatitis, multiple organ failure in the early stage after onset, and sepsis in the late stage, due to infection of pancreatic or peripancreatic devitalized tissue, contribute to its high mortality. In analogy with sepsis, evidence has accumulated of the significance of apoptotic cell death in the systemic manifestations associated with acute pancreatitis. Since we identified apoptosis-inducing activity in pancreatitis-associated ascitic fluid in 1995, a number of investigators, including ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 61 publications
3
48
0
3
Order By: Relevance
“…For example, nonpancreatic organ injury/dysfunction in AP is primarily due to apoptotic rather than necrotic epithelial cell death (74) and may be accentuated by administration of an apoptosis inducer. Hence, strategies to reduce the severity of AP by inhibiting necrosis and enhancing apoptosis may require selective targeting of pancreatic rather than nonpancreatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nonpancreatic organ injury/dysfunction in AP is primarily due to apoptotic rather than necrotic epithelial cell death (74) and may be accentuated by administration of an apoptosis inducer. Hence, strategies to reduce the severity of AP by inhibiting necrosis and enhancing apoptosis may require selective targeting of pancreatic rather than nonpancreatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Caspases not only mediate apoptosis but also protect cells against necrosis by cleavage and inactivation of PARP or trypsin (55). Perhaps paradoxically, intracellular heat shock proteins (HSPs) protect pancreatic acinar cells partly by inhibition of apoptosis (56,57), suggesting a pathogenic role of apoptosis in AP (58). Subsequently, researchers also observed that pancreatic acinar cells undergoing apoptosis can release histones, DNA and HMGB1, which facilitate pancreatic injury and the inflammatory response (10,11).…”
Section: Apoptosismentioning
confidence: 99%
“…There is a kind of substantial distinction between apoptosis and necrosis (Samuilov et al, 2000). The extent of apoptosis is associated with SAP-induced multiple organ injury (Takeyama, 2005;Zhang et al, 2007c). Salvia miltiorrhiza ('Danshen' in Chinese) injection and dexamethasone injection are representative traditional Chinese and Western medicines, respectively, most frequently used for the treatment of SAP patients.…”
mentioning
confidence: 99%
“…These compounds can protect endothelial cells, and prevent inflammation, lipid peroxidation, and calcium overload (Kim et al, 2005;Li et al, 2006;Ding and Yuan, 2007;Lam et al, 2007;Zhao et al, 2008). Studies have proved that Salvia miltiorrhiza can mitigate the pathological changes in the liver, lung, kidney, intestine, and stomach of SAP rats, and prevent the occurrence of multiple organ failure (Zhang et al, 2002a;2002b;2002c;2005). Dexamethasone has anti-inflammatory, anti-toxic, and anti-shock effects.…”
mentioning
confidence: 99%